Intensive group therapy program for stutterers:-a report - GeethaY.V., Manjula R (Journal of All India Institute of Speech and Hearing, 1970)
In rehabilitation programs of stuttering, a  variety of techniques have been tried during the past few decades to facilitate fluent speech. Most of these programs have focussed on individualized training with little opportunities provided for the stutterers to interact with others, apart from the therapist. The fluent speech thus achieved during the individual clinical situation is hardly maintained in extra clinical situations and speech therapists too are unable toprovide sufficient guidance in this area due to lack of resources, access to and control over real life situations. Even when, follow-up and maintenance guidelines are advised, it is not always possible to monitor the same.